Wetlands Ecology and Management - Wetlands Ecology and Management (Springer Nature, 2026)
Wetlands Ecology and Management is an international journal that publishes authoritative and original articles on topics relevant to freshwater, brackish and marine coastal wetland ecosystems. The Journal serves as a multi-disciplinary forum covering key issues in wetlands science, management, policy and economics. As such, Wetlands Ecology and Management aims to encourage the exchange of information between environmental managers, pure and applied scientists, and national and international authorities on wetlands policy and ecological economics.
FI 0.39
Q4
Keywords: Life Sciences; Freshwater Ecology; Acuerdos transformativos; Transformative agreements; Ecología de humedales; Gestión ambiental; Ecosistemas acuáticos